Immune system disturbances after a new coronavirus infection COVID-19 - T. V. Glazanova; E. R. Shilova (Журнал инфектологии)
During the pandemic, a large number of works devoted to COVID infection have appeared, which have made it possible to understand the pathogenetic features of the disease and to accumulate significant clinical experience. However, the question remains about the degree of participation of humoral and cellular (primarily T-cell) immunity in the mechanisms of immune defense and resistance to COVID-19, the individual features of the immune response in different subjects. Post-COVID syndrome is currently a separate diagnosis included in the ICD-10 International Classification of Diseases, but the long-term effects of the SARS-CoV-2 on the immune system are not yet well established. At the same time, a long-term increased activity of the immune system can contribute to the development of autoimmune reactions. The review of the literature presents the results of studies, mainly devoted to immune system disorders after COVID infection. The changes in subpopulations of T-lymphocytes, B-lymphocytes, their functional properties, the complement system and other factors of humoral immunity, as well as the production of a number of cytokines are described. Data on immune disorders in post-COVID syndrome and during the convalescence period are presented in detail. Since COVID-19 is an infection that has a significant impact on the hematopoietic system and hemostasis, special attention is paid to the category of subjects with an increased risk of severe complications. Among the latter are elderly patients, persons suffering from diabetes mellitus, oncological and oncohematological patients, in particular, with hematopoietic and lymphoid tissue neoplasia, such as chronic lymphocytic leukemia, lymphoma, multiple myeloma. The review pays special attention to the peculiarities of the course of COVID-19 and the response of the immune system to vaccination in patients with oncohematological diseases. Deciphering the significance of individual links of cellular and humoral immunity in patients who have undergone COVID-19 is an important issue in creating effective vaccines and improving therapeutic methods.